THE RECEPTION OF A CONTROVERSIAL PLAY – EVANGHELISTII – IN POST-COMMUNIST ROMANIAN SOCIETY - CARMEN D. CARAIMAN (Challenges of the Knowledge Society)
In this paper we intend to present the reception of the play Evangheliştii [The Evangelists] (published in volume in 1993 and represented on stage in 2005) written by Alina Mungiu Pippidi in post-communist Romanian society. In the interpretation of this topic we have considered the author’s artistic goals in relation to the “horizon of expectation” of the Romanian theatre public, as well as to the reaction that critics and institutions outside the world of theatre, such as the Orthodox and Catholic Churches, and local public institutions, had as regards its publication and stage representation. Thus, we have pointed out the clash and the gap that exist between the author’s postmodernist approach to religious faith (i.e. the deconstruction of the Christian ideology) and the often wrong reception of the play’s topic coming basically from the Church and in part from the theatre audience. The reception of this play in post-communist Romania is analysed in relation to the rigid, formalist perspective on art shared by an important part of the theatre audience. One of the main conclusions we have drawn is that the openness degree of our society members to the freedom of artistic creation illustrates, in fact, the degree of civilization and, implicitly, of tolerance which we have acquired up to a certain point in time as a society, especially that today our country is no longer totalitarian and, in consequence, no artistic manifestation can be censored by any ideologies coming from the public space.